Optimal scheduling of integrated energy systems with a ladder-type carbon trading mechanism and demand response - Shi, Linjun; Liang, Changyu; Zhou, Jianhua; Li, Yang; Liu, Jian; Wu, Feng (Frontiers in Energy Research, 2024)
To achieve the "dual carbon" goal, the integrated energy system(IES) needs to take into account both economic and low-carbon requirements while meeting the growing energy demand. Therefore, an optimal scheduling model for low-carbon economic operation is proposed. Firstly, a more accurate carbon emission model is used to consider the actual carbon emission of gas load, to improve the original carbon emission model. A ladder-type carbon trading mechanism is introduced to further constrain the carbon emission of IES. Then, the demand-side response model is proposed, which uses the time-of-use price and mutual substitution of electricity, heat, and gas loads to curtail, time-shift, and substitute the load. Finally, an optimal scheduling model with minimum energy purchase cost, wind and photovoltaic curtailment cost, demand response cost, and carbon emission cost is constructed, which is solved by the GUROBI solver. Through comparative simulation analysis of 6 cases, the results show that the objective function considers the traditional carbon trading cost to reduce carbon emission by about 19.3 % compared with the case without considering. After adopting the ladder-type carbon trading mechanism, the carbon emission of IES can be further limited by about 0.35 %, and the appropriate carbon trading base price is explored. In addition, after the demand response, the energy purchase cost, carbon trading cost, and carbon emission of IES are reduced by about 3.4 %, 18.5 %, and 36.2 %, respectively, compared with those before the demand response. The simulation results verify the effectiveness of the proposed model.